2010
DOI: 10.1186/2049-6958-5-4-244
|View full text |Cite
|
Sign up to set email alerts
|

Six minute walking distance in kyphoscoliosis patients with chronic respiratory failure

Abstract: AimTo evaluate kyphoscoliosis patients with chronic hypercapnic respiratory failure (CHRF) using the six minute walk test (6MWT) distance (6MWD) and cardio-pulmonary function tests.MethodThis prospective cross-sectional study was carried out in a tertiary training and research hospital in Turkey. Kyphoscoliosis patients with CHRF on home mechanical ventilation (HMV) followed in a respiratory intensive care unit (RICU) out-patient clinic were enrolled. Patients' demographics were recorded as well as transthorac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
9
1
1
Order By: Relevance
“…Observed levels were significantly lower than found in literature, most probably as a result of chronic respiratory problems (Karakurt et al, 2010;Li et al, 2005;. The physical conditions of children gradually improved during the stay in sanatorium and at the end of their stay, the 6MWT levels were significantly better.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Observed levels were significantly lower than found in literature, most probably as a result of chronic respiratory problems (Karakurt et al, 2010;Li et al, 2005;. The physical conditions of children gradually improved during the stay in sanatorium and at the end of their stay, the 6MWT levels were significantly better.…”
Section: Discussioncontrasting
confidence: 48%
“…Our finding of 6MWT in the glucansupplemented group were better than in the placebo group and correspond well with the improvements in salivary immunity. As the overall regime of children, including physical challenges, organized rest and nutrition, are identical in both groups, the observed changes were not influenced by these outside parameters (Casanova et al, 2011;Karakurt et al, 2010;Lehne et al, 2005). Therefore, we can conclude that 6MWT test represents a solid tool for measurements of the success of complex spa treatment and glucan supplementation (Lehne et al, 2005;Li et al, 2007).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Body mass index (BMI) and age have been negatively correlated with 6MWD, but no correlation has been found with the level of arterial blood gases. Karakurt et al [12] have reported that patients with kyphoscoliosis walked a much shorter distance than they ought to (median 270 m -43.7% of predicted distance) [12]. Oxygen supplementation at the beginning and during the 6MWT did not elongate 6MWD, but long-term therapy with non-invasive ventilation (NIV) was found to have a significant positive effect [4].…”
Section: Exercise Training and Respiratory Rehabilitationmentioning
confidence: 99%
“…We have previously shown that by using reference equations (age, sex, and BMI), pulmonary functions in kyphoscoliosis patients with chronic hypercapnic respiratory failure and on home NIV are better correlated with percent-ofpredicted 6MWD than with actual 6MWD. 12 In current clinical practice the distance walked is the only crucial factor for physicians when making clinical judgments on patients with cardiopulmonary diseases. The actual 6MWD uses only the number of meters walked, but the walking distance is dependent on various factors such as age, sex, and BMI.…”
Section: Introductionmentioning
confidence: 99%